PERAN KEPERCAYAAN DALAM MEMODERASI PENGARUH PERSEPSI RISIKO DAN LITERASI DIGITAL TERHADAP ADOPSI QRIS PADA GENERASI Z DI KABUPATEN SIDOARJO - Ahmad Bima Firnanda; Muhadjir Anwar; G. Oka Warmana (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to analyze the influence of risk perception and digital literacy on the adoption of QRIS (Quick Response Code Indonesian Standard), with trust as a moderating variable among Generation Z in Sidoarjo Regency. This study adopts the Technology Acceptance Model (TAM) as its theoretical framework. A total of 100 respondents were selected using purposive sampling. The data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results show that both risk perception and digital literacy have a positive and significant effect on the adoption of QRIS. However, trust does not significantly moderate the relationship between risk perception or digital literacy and QRIS adoption. These findings suggest that trust neither strengthens nor weakens the influence of the two independent variables on QRIS adoption among Generation Z in Sidoarjo Regency.